A new species of Notocupes (Coleoptera: Archostemata) from the Lower Cretaceous (Albian) Jinju Formation in South Korea. (December 2022) - Lee, Soo Bin; Nam, Gi Soo; Li, Yan-Da
Abstract: Notocupes premeris sp. nov., is reported from the Lower Cretaceous (Albian) Jinju Formation, representing the first complete body fossil of Notocupes from the Korean Peninsula. The new species is characterized by the broad body shape (e.g., ventrite 5 about 1.8 times as wide as long), about 30 cells maximum per row on elytra, and the somewhat V-shaped anterior pronotal edge. The species assignment of the previously reported Zygadenia elytron from North Korea is also discussed.